Supramolecular adducts of mesocyclic diamines with various carboxylic acids: Charge-assisted hydrogen-bonding in molecular recognition - Wei Guo; Xiaojuan Fu; Jing Chen (Journal of Saudi Chemical Society, 2020)
Aggregation of saturated mesocyclic diamine 1,4-diazacycloheptane (dach) or piperazine (pipz) and diversiform carboxylic acids with mono- or di-carboxyls yields a series of novel binary supramolecular adducts via two-point molecular recognition. All the supramolecular assemblies were obtained by solvent evaporation method from different media. X-ray single-crystal diffraction analyses reveal that these supramolecular moieties present 1D chain motif, 2D flat, corrugated sheet structures and 3D CdSO4, pillar-layered networks through carboxylate-amide N–H⋯O, as well as its proton transfer form N+–H⋯O−, carboxyl head to tail O–H⋯O, and extended hydrogen-bonding interactions. Their compositions and structures were also confirmed by Fourier transform infrared (FT-IR) spectroscopy. Thermal stability of these binary crystalline adducts has been investigated by thermogravimetric analysis (TGA), suggesting similar thermal stabilities.